The value of processing sorghum grain for finishing swine - B A Koch; G L Allee; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1971)
Three feeding trials were conducted to determine benefits of processing sorghum grain (milo) for finishing swine. Flaked, ground, and dry rolled milo rations resulted in similar pig weight gains. Generally, the feed:gain ratios of pigs receiving steam-flaked rations were slightly better than ratios of pigs receiving ground or dry rolled grain. Pigs receiving a popped ration grew significantly slower and less efficiently than pigs receiving ground or flaked rations. Grinding the popped ration increased average daily feed intake and average daily gain, but the feed:gain ration did not improve. Finishing swine can be fed steam-flaked milo very satisfactorily; however, the cost of processing the milo more than offset the advantages in feed efficiency.; Swine Day, Manhattan, KS, October 7, 1971
Keywords: Swine day; 1971; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 181; Swine; Sorghum grain; Finishing pigs; Milo; Feed/gain